2005
DOI: 10.1158/0008-5472.can-04-4072
|View full text |Cite
|
Sign up to set email alerts
|

Perillyl Alcohol Inhibits a Calcium-Dependent Constitutive Nuclear Factor-κB Pathway

Abstract: The cell death induced by the monoterpene anticancer agent perillyl alcohol correlates to the increased expression of certain proapoptotic genes known to influence cell survival. Whereas sequence-specific DNA-binding factors dictate the expression patterns of genes through transcriptional regulation, those transcriptional factors influencing constitutive cell survival with perillyl alcohol treatment are not well studied. Here, we investigated whether the monoterpenes can regulate the activity of nuclear factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 46 publications
2
36
0
2
Order By: Relevance
“…This drug has been reported to inhibit cancer cell growth and to enhance the pro-apoptotic effects of combined chemotherapeutic drugs such as bortezomib or cisplatin in several malignant tumors including MCL. 13,25,26 We have shown herein POH (1mM), or the combination of bortezomib (100nM) and POH (1mM) for 16 hours. Nuclear extracts from untreated, bortezomib-treated, POH-treated, and combination-treated CD45 ϩ CD19 Ϫ MCL-ICs were analyzed using ELISA assays to assess p50 and p65 DNA-binding activities.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This drug has been reported to inhibit cancer cell growth and to enhance the pro-apoptotic effects of combined chemotherapeutic drugs such as bortezomib or cisplatin in several malignant tumors including MCL. 13,25,26 We have shown herein POH (1mM), or the combination of bortezomib (100nM) and POH (1mM) for 16 hours. Nuclear extracts from untreated, bortezomib-treated, POH-treated, and combination-treated CD45 ϩ CD19 Ϫ MCL-ICs were analyzed using ELISA assays to assess p50 and p65 DNA-binding activities.…”
Section: Discussionmentioning
confidence: 83%
“…13,25,26 TG2 is a calcium-dependent cross-linking enzyme and, in addition to calcium, catalyzes the polymerization of IB␣. 37,38 We hypothesized that calcium blockers inhibit NF-B activation by inhibiting TG2 function.…”
Section: Calcium Blockers Inhibit Nf-b Activation and Tg2 Activity Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Several isolated substances of aromatic plants demonstrated remarkable pharmacological actions through inhibition of NF-kB activity, as 4-nerolydilcathecol. Previous studies have shown that limonene, perillyl alcohol and menthol inhibited the activation of NF-қB (Berchtold et al, 2005;Salminen et al, 2008). α-Pinene, which is also a monoterpene, revealed a robust activity by inhibiting translocation of NF-қB to the cell nucleus, increasing the expression of the inhibitory protein IқB (Zhou et al, 2004).…”
Section: In Vitro Inhibition Of Nuclear Factor Kappa Bmentioning
confidence: 99%
“…This therapeutic phase I trial showed limited promising results (Ripple et al 2000). We later discovered that POH inhibited the antiapoptotic ability of cancers via a calcium channel interaction that led to the downregulation of NFkB (Berchtold et al 2005). This mechanism of action could underlie the cytostatic and cytotoxic actions of POH toward both premalignant and malignant cells.…”
mentioning
confidence: 99%